2014
DOI: 10.1186/s12913-014-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of Western Australia computed tomography utilisation patterns and their policy implications

Abstract: BackgroundComputed tomography (CT) scanning is a relatively high radiation dose diagnostic imaging modality with increasing concerns about radiation exposure burden at the population level in scientific literature. This study examined the epidemiology of adult CT utilisation in Western Australia (WA) in both the public hospital and private practice settings, and the policy implications.MethodsRetrospective cohort design using aggregate adult CT data from WA public hospitals and Medical Benefits Schedule (MBS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Findings may not generalize beyond the single, large metropolitan medical imaging department study setting. However, the age and gender profile of the sample was similar to that of participants in other large Australian (38,39) and international studies (40,41) with medical imaging outpatients.…”
Section: Discussionsupporting
confidence: 59%
“…Findings may not generalize beyond the single, large metropolitan medical imaging department study setting. However, the age and gender profile of the sample was similar to that of participants in other large Australian (38,39) and international studies (40,41) with medical imaging outpatients.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, data from public hospitals are omitted from this analysis. An earlier cohort study using data from Western Australia found that 74% of CT scans performed from 2006/7 through 2011/12 were billed to Medicare, rather than delivered in a public hospital (2). This analysis found differences between CT in public and private settings.…”
Section: Discussionmentioning
confidence: 91%
“…Previous work in Western Australia found the greatest changes per 1,000 population from 2006/7 to 2011/12 were for interventional CT (7.3 to 11.4), followed by facial bones (8.3 to 9.7) (2). MBS-billed CT of the spine reduced from 20.8 to 18.8 per 1,000 population(2).While the proportionate contribution of population size increased over the study period, the change in population distribution explains less than 10% of the change in CT count and cost over all compared time periods included in the analysis, despite a shift to the right. However, this is relative to population growth and non-population size/distribution factors and it is clear that some changes in CT distribution have occurred, including an increase in CT for those aged 85 years or above.…”
mentioning
confidence: 89%
“…More recent reports indicate that computed tomography (CT) now tends to be ordered in preference to other modalities for the evaluation of abdominal issues [ 17 , 23 ]. Older people are major CT users in Australia and elsewhere [ 17 , 23 , 24 ]. In the USA for example, 11% of all emergency department presentations for abdominal pain have CT scans,[ 23 , 24 ] and its use has increased tenfold between 1997 and 2016, while the utilisation of abdominal ultrasound plateaued between 1997 and 2011 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%